When Two Worlds Collide: The Contribution and Association Between Genetics (APOEε4) and Neuroinflammation (IL-1β) in Alzheimer’s Neuropathogenesis - Jagadeesh Narasimhappagari; Ling Liu; Meenakshisundaram Balasubramaniam; Srinivas Ayyadevara; W. Sue T. Griffin (Cells)
Introduction: Here we consider the collision of a genetic factor and an essential instigator in Alzheimer’s neuropathogenesis: (i) the Alzheimer’s gene (APOEε4), which downregulates lysosomal autophagy and induces synthesis of (ii) the instigator, interleukin-1β (IL-1β), which drives synthesis of βAPP for Aβ plaques and of MAPKp38 for phosphorylation of tau for formation of neurofibrillary tangles (NFTs), the two cardinal features of AD. Methods: RT-PCR, immunoblotting and immunohistochemistry techniques were used to assess the levels of IL-1β and its signaling cascade in ADε4,4, ε3,3, and age-matched controls (AMC3,3) in hippocampal regions of the brain. Results: IL-1β and its downstream signaling proteins TLR-2, MyD88, NFκB, COX-1, and COX-2 were greater in tissues from ADε4,4 than ADε3,3 or AMC3,3. Cathepsin B, D, and L levels, which play a pivotal role and are necessary for lysosomal autophagy, were lower in ADε4,4 than in ADε3,3 or AMC ε3,3. IL-1β and its downstream signaling cascade TLR-2, MyD88, NFκB, COX-1, and COX-2 expression levels were high in SH-SY5Y and T98G cells transfected with APOεE4. Conclusions: APOEε4 causes Alzheimer’s by downregulating autophagy, thus inducing IL-1β for Aβ plaque and neurofibrillary tangle formation.